Proposing a culture-centered approach to career scholarship: The example of subsistence careers in the US Arctic. (December 2015) - Mitra, Rahul
In this article, I draw from the culture-centered approach to explore contemporary negotiations of career and work, positing career as a form of cultural practice. Rooted in postcolonial theory and subaltern studies, the culture-centered approach examines the active accomplishment of culture through everyday communicative practices, amidst the structural conditions that frame lived experiences, and focusing specifically on marginalized groups. I first trace how culture is conceptualized in extant career studies, in the psychological, sociological and communicative streams. Identifying both key gaps and paradoxes in the literature, I outline the culture-centered approach, suggesting four key principles to reconceive career as cultural practice. Specifically: career draws on both structure and action; career agency is hybridized across individuals/collectives; career agency is layered and contested; and career is both discursive and material. The framework is illustrated using an example from an ongoing study on the negotiation of subsistence careers by Native Alaskans in the US Arctic.